An alternative splicing signature in human Crohn’s disease - Li, Daowei; Liang, Yuanzi; Lu, Jia; Tan, Yue (BMC gastroenterology, 2021)
Background Although hundreds of risk loci for Crohn's disease (CD) have been identified, the underlying pathogenesis of CD remains unclear. Recently, evidence has shown that aberrant gene expression in colon tissues of CD patients is associated with the progression of CD. We reasoned that post-transcriptional regulation, especially alternative splicing (AS), may also play important roles in the pathogenesis of CD. Methods We re-analyzed public mRNA-seq data from the NCBI GEO dataset (GSE66207) and identified approximately 3000 unique AS events in CD patients compared to healthy controls. Results "Lysine degradation" and "Sphingolipid metabolism" were the two most enriched AS events in CD patients. In a validation study, we also sequenced eight subjects and demonstrated that key genes that were previously linked to CD, such as IRF1 and STAT3, also had significant AS events in CD. Conclusion Our study provided a landscape of AS events in CD, especially as the first study focused on a Chinese cohort. Our data suggest that dysregulation of AS may be a new mechanism that contributes to the pathogenesis of CD. Keywords: Alternative splicing, Crohn's disease, Post-transcriptional regulation